2007
DOI: 10.1111/j.1439-0426.2007.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Chelidonichthys obscurus and Chelidonichthys lastoviza (Pisces: Triglidae) from the Gulf of Gabes (Tunisia)

Abstract: Summary The most common gurnard species in the Gulf of Gabes (Tunisia) are Chelidonichthys lastoviza and C. obscurus. These two species were collected by trawl nets between February 2000 and July 2002 at depths ranging from 80 to 150 meters. In the laboratory the stomach contents were examined for diet assessment and to determine diet variation in relation to fish size, season and sex. The importance of different prey items was analysed utilising several feeding indexes, while diet overlap was tested using Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Gary and Ellis (2014) obtained a total of 82 specimens of C. obscurus that were caught in the English Channel, all from 2004 to 2013. To date, little is known about the biology of C. obscurus, and most published data are from the western Mediterranean Sea, where there have been studies of their reproductive biology (Munoz et al, 2003, as Aspitrigla obscura) and feeding habits (Moreno-Amich 1996;Morte et al, 1997;Boudaya et al, 2007) and parasites (Serecca et al, 2013). Genetic analysis should also be conducted on these existent populations to determine their genetic structure as defined for other marine species (Turan, 2006;Turan, 2008).…”
Section: Conservation Recommendationsmentioning
confidence: 99%
“…Gary and Ellis (2014) obtained a total of 82 specimens of C. obscurus that were caught in the English Channel, all from 2004 to 2013. To date, little is known about the biology of C. obscurus, and most published data are from the western Mediterranean Sea, where there have been studies of their reproductive biology (Munoz et al, 2003, as Aspitrigla obscura) and feeding habits (Moreno-Amich 1996;Morte et al, 1997;Boudaya et al, 2007) and parasites (Serecca et al, 2013). Genetic analysis should also be conducted on these existent populations to determine their genetic structure as defined for other marine species (Turan, 2006;Turan, 2008).…”
Section: Conservation Recommendationsmentioning
confidence: 99%
“…The tub gurnard ( Trigla lucerna L.) is a teleost species of commercial importance to fishing nations bordering the Atlantic and Mediterranean. Tub gurnard has been investigated for farming, and studies have been carried out on its reproduction, larval rearing and performance . Results concerning the productive performance of T. lucerna in aquaculture and the lack of knowledge about its genetic population structure have prompted evaluations of its genetic variability.…”
Section: Source/descriptionmentioning
confidence: 99%
“…Park et al (2017) also found that these crustaceans dominated the diets of Roundsnout Gurnard and Butterfly Gurnard L. vanessa (except larger individuals of Butterfly Gurnard) in northeastern Tasmania. Such a focus on epibenthic crustaceans was also recorded for Grooved Gurnard and Australian Spiny Gurnard L. papilio from southwestern Australia (Platell and Potter 1999); the gurnard Chelidonichthys (Aspitrigla) cuculus, Large-Scaled Gurnard L. cavillone, and Streaked Gurnard Chelidonichthys (Trigloporus) lastoviza from the Cyclades and Dodecanese Islands (eastern Mediterranean; Terrats et al 2000); Longfin Gurnard C. obscurus and Streaked Gurnard from the Gulf of Gabes, Tunisia (Boudaya et al 2007); and Spiny Red Gurnard C. spinosus and Redbanded Searobins L. guentheri from southeastern Korea (Huh et al 2007;Baeck et al 2011).…”
Section: Speciesmentioning
confidence: 99%
“…The diets of gurnards have been studied worldwide (e.g., Ross 1978;Moreno-Amich 1992, 1996Terrats et al 2000;Boudaya et al 2007;Huh et al 2007;Baeck et al 2011), with interspecific partitioning of resources recorded among species in the northwestern Atlantic (Ross 1977), the Mediterranean Sea (Labropoulou and Machias 1998), southwestern Australia (Platell and Potter 1999), and the Cantabrian Sea (Lopez-Lopez et al 2011). Despite their economic and ecological importance in southeastern Australia, little is known about the dietary habits of the species in this region.…”
mentioning
confidence: 99%